Insights into Indonesian Students’ Willingness to Communicate in English in the Classroom - Maranatha, Maria; Sengkey, Virginia Gabrella (Universitas Lancang Kuning, 2023)
English learners need to be willing to communicate in English for them to learn the language successfully. Considering that English has been taught since elementary school in Indonesia, it is interesting to identify how willing students are to communicate in English, especially in secondary school. Thus, this study aimed to know the secondary school students’ willingness to communicate in English in terms of using English in the classroom and linguistic and non-linguistic factors. Furthermore, this study identified whether there was a significant difference based on gender and grade levels. This study used a quantitative method with a descriptive and comparative design. This study was conducted at a private secondary school, with 95 respondents recruited via convenience sampling. As a result, students’ willingness to communicate in terms of using English in the classroom was medium, indicating that students were willing enough to communicate in English. Specifically, the students’ willingness to communicate in terms of linguistic and non-linguistic factors was medium. This shows that students were willing enough to use English regarding linguistic and non-linguistic factors. Moreover, there was no difference based on gender but a significant difference based on grade level, with the highest mean score of 75.55 in grade 7. Thus, since students are willing enough to communicate in English, teachers need to find strategies to help the students to be very willing to communicate in English, especially secondary school students at higher grade levels. Also, future studies on WTC must be done in different regions in Indonesia by considering WTC other factors such as parental involvement, teachers, socio-economic status, anxiety, motivation, or other environment-related factors at various levels or schools.